2013
DOI: 10.1111/sms.12161
|View full text |Cite
|
Sign up to set email alerts
|

Specific muscle–tendon architecture in elite Kenyan distance runners

Abstract: The Achilles tendon moment arm (MA_AT) and foot lever ratio (FLR) can play important roles for force production and movement economy during locomotion. This notion has become more relevant, and suggestion has been given that the Kenyan runners belonging to the world elite would have specific anatomical, mechanical, and functional properties in their lower limbs and that this feature could be responsible for their high running economy. The present study aimed to characterize the AT of elite Kenyan distance runn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 27 publications
(36 reference statements)
5
44
1
1
Order By: Relevance
“…It is possible that subjects with favorable muscle-tendon properties for endurance or sprint running were more likely to participate in such activities. However, we did not observe differences between older trained and untrained subjects in genetically determined variables such as Achilles tendon moment arm, forefoot length or Achilles tendon length, all of which are related to running performance (3,25,26,42). This suggests that selection bias caused by genetic predisposition towards favorable musculoskeletal properties for running did not considerably affect our data, although the possibility of selection bias cannot be completely excluded.…”
Section: Methodological Considerationsmentioning
confidence: 57%
“…It is possible that subjects with favorable muscle-tendon properties for endurance or sprint running were more likely to participate in such activities. However, we did not observe differences between older trained and untrained subjects in genetically determined variables such as Achilles tendon moment arm, forefoot length or Achilles tendon length, all of which are related to running performance (3,25,26,42). This suggests that selection bias caused by genetic predisposition towards favorable musculoskeletal properties for running did not considerably affect our data, although the possibility of selection bias cannot be completely excluded.…”
Section: Methodological Considerationsmentioning
confidence: 57%
“…Often, the F z moment arm length is interpolated from known forefoot length. In this case, the ratio of forefoot length to AT moment arm is referred to as the foot lever ratio (Kunimasa et al, 2014). The F z moment arm can be altered by changing ankle joint kinematics during the stance phase.…”
Section: Factors Not Affected By Trainingmentioning
confidence: 99%
“…As previously suggested however, the elevated AT force associated with a shorter moment arm may also incur a substantial muscle energy cost (Fletcher and MacIntosh, 2015) and as such, a longer AT moment arm may help reduce E run by reducing the required muscle force and level of muscle activation to sustain a given joint moment. To support this hypothesis, elite Kenyan long-distance runners, a population known for their exceptionally-low E run (Larsen, 2003; Wilber and Pitsiladis, 2012), have longer AT moment arm lengths and shorter forefoot lengths compared to similarly-trained Japanese distance runners (Kunimasa et al, 2014). van Werkhoven and Piazza (2017) recently found a significant relationship between peak Achilles tendon force and heel length, suggesting subjects with shorter heels experience larger Achilles tendon forces.…”
Section: Factors Not Affected By Trainingmentioning
confidence: 99%
“…Previous studies have reported that absolute upper and lower legs in the East African endurance runners, who have superior running performance and running economy, are longer than those in endurance runners of other regions (Kunimasa et al, 2014;Lucia et al, 2006;Sano et al, 2015;Verillo et al, 2013). Additionally, Mooses et al (2015) determined a positive correlation between absolute upper leg length and running performance in Kenyan endurance runners.…”
Section: Introductionmentioning
confidence: 96%